Hydrologic regime and herbivory stabilize an alternative state in Yellowstone National Park - Wolf, Evan C., author; Cooper, David J., author; Hobbs, N. Thompson, author; Ecological Society of America, publisher (Rangifer, 2016)
A decline in the stature and abundance of willows during the 20th century occurred throughout the northern range of Yellowstone National Park, where riparian woody-plant communities are key components in multiple-trophic-level interactions. The potential causes of willow decline include climate change, increased elk browsing coincident with the loss of an apex predator, the gray wolf, and an absence of habitat engineering by beavers. The goal of this study was to determine the spatial and temporal patterns of willow establishment through the 20th century and to identify causal processes. Sampled willows established from 1917 to 1999 and contained far fewer young individuals than was predicted from a modeled stable willow population, indicating reduced establishment during recent decades. Two hydrologically distinct willow establishment environments were identified: fine grained beaver pond sediments and coarse-grained alluvium. Willows established on beaver pond sediment earlier in time, higher on floodplain surfaces, and farther from the current stream channel than did willows on alluvial sediment. Significant linear declines from the 1940s to the 1990s in alluvial willow establishment elevation and lateral distance from the stream channel resulted in a much reduced area of alluvial willow establishment. Willow establishment was not well correlated with climate-driven hydrologic variables, but the trends were consistent with the effects of stream channel incision initiated in ca. 1950, 20-30 years after beaver dam abandonment. Radiocarbon dates and floodplain stratigraphy indicate that stream incision of the present magnitude may be unprecedented in the past two millennia. We propose that hydrologic changes, stemming from competitive exclusion of beaver by elk over browsing, caused the landscape to transition from a historical beaver-pond and willow mosaic state to its current alternative stable state where active beaver dams and many willow stands are absent. Because of hydrologic changes in streams, a rapid ...